2021
DOI: 10.1016/j.icarus.2020.114125
|View full text |Cite
|
Sign up to set email alerts
|

“Water” abundance at the surface of C-complex main-belt asteroids

Abstract: Recently published space-based observations of main-belt asteroids with the AKARI telescope provide a full description of the 3-µm band, related to the presence of OH bearing minerals. Here, we use laboratory spectra of carbonaceous chondrites obtained under controlled atmosphere (CI,CM,CO,CV,CR Tagish Lake) to derive spectral metrics related to the water content in the samples. After testing several spectral metrics, we use a combination of band depth at 2.75 µm and 2.80 µm that shows a correlation with [H2O]… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…Within 10 au, objects of tens of km will become devoid of both free water and that embedded in rocks; large 100 km bodies may be able to retain a fraction of the embedded water. However, even for the relatively water-rich C-type asteroids, only 10% of their mass is contained in water (see a recent discussion by Beck et al 2021). Thus the loss of water will not affect the accretion rate significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Within 10 au, objects of tens of km will become devoid of both free water and that embedded in rocks; large 100 km bodies may be able to retain a fraction of the embedded water. However, even for the relatively water-rich C-type asteroids, only 10% of their mass is contained in water (see a recent discussion by Beck et al 2021). Thus the loss of water will not affect the accretion rate significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The visible and near-infrared (IR) reflectance spectra of heated CM chondrites closely resemble some low albedo C-type asteroids (Hiroi et al 1993(Hiroi et al , 1996Cloutis et al 2012), although it has been suggested that rather than being dehydrated these bodies never experienced widespread aqueous alteration (Vernazza et al 2015;Rivkin et al 2019). Nevertheless, estimates of the surface water content of many C-type asteroids fall within the range of heated CM chondrites (Rivkin et al 2003;Beck et al 2021). These relationships suggest that materials mineralogically and compositionally similar to heated CM chondrites could be a major constituent of the regolith on primitive asteroids.…”
Section: Introductionmentioning
confidence: 92%
“…rich in C, H, N, and O (Miyamoto & Zolensky 1994;Burbine et al 2002) that could have been relevant to habitability (Kwok 2016). Among CCs, CI (Ivuna-type) and CM (Migheitype) chondrites are of particular interest since they contain a prominent 3-µm OH absorption band, indicating aqueous alteration on their parent bodies (Lebofsky et al 1981;Beck et al 2010;Cloutis et al 2011a,b;Takir et al 2013;McAdam et al 2015;Beck et al 2021b). It is hard to directly compare asteroids and meteorites primarily due to the possible difference in sampling regions (i.e., observed asteroidal surfaces susceptible to space weathering in contrast to meteorites originating from any parts of the parent bodies) and observing geometry (Hiroi et al 2001;Jedicke et al 2004).…”
Section: Comparison With Carbonaceous Chondritesmentioning
confidence: 99%